Autophagy and porcine circovirus infection: a mini review - Chen, Xiaoyong; Chen, Xi; Yu, Ziding (Frontiers in Cellular and Infection Microbiology, 2025)
Porcine circovirus (PCV), particularly PCV type 2 (PCV2), is a major pathogen driving porcine circovirus-associated diseases (PCVAD), causing significant economic losses in the swine industry. Accumulating evidence highlights autophagy as a critical host-pathogen interface during PCV infection. PCV2 activates autophagy through reactive oxygen species (ROS)-mediated signaling and metabolic regulators like the AMP-activated protein kinase (AMPK)/mechanistic target of rapamycin (mTOR) axis, creating a conducive environment for viral persistence. Concurrently, this virus exploits ubiquitin ligases to induce ubiquitination of cellular immune factors, promoting selective autophagy for immune evasion. Host factors, such as retinol-binding protein 4 (RBP4), act as restriction factors by counteracting viral strategies through autophagy modulation. Environmental stressors could exacerbate PCV2 pathogenesis by amplifying ROS-dependent autophagy, while interventions like taurine mitigate viral replication via ROS/AMPK/mTOR pathway inhibition. This mini-review synthesizes current understandings of PCV-autophagy crosstalk, emphasizing its critical role as a host vulnerability and therapeutic target. Understanding the intricate interplay between autophagy and PCV infection may unveil novel therapeutic targets, such as autophagy modulators, to mitigate viral replication and immune pathology.